2020
DOI: 10.1101/2020.06.02.130567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequent assembly of chimeric complexes in the protein interaction network of an interspecies yeast hybrid

Abstract: Hybrids between species often show extreme phenotypes. The molecular determinants underlying such phenotypes are yet to be comprehensively explored. In this study, we investigated the phenotypes of an interspecies diploid hybrid in terms of protein-protein interactions detected by protein correlation profiling. We used two yeast species, Saccharomyces cerevisiae and Saccharomyces uvarum , which are interfertile, but yet have proteins diverged enough to be differentiated using mass spectrometry. Most of the pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The genomes of S. cerevisiae and S. kudriavzevii are in general collinear and gene content is largely overlapping. Furthermore, the first indication of genetic compatibility has shown that macromolecular complexes between proteins from the different sub-genomes can be formed but at a very low frequency [73, 74], meaning that the two sub-genomes act largely as two separate entities. With these properties and with the fact that very little data is available for hybrids, S. cerevisiae makes a good proxy for the hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…The genomes of S. cerevisiae and S. kudriavzevii are in general collinear and gene content is largely overlapping. Furthermore, the first indication of genetic compatibility has shown that macromolecular complexes between proteins from the different sub-genomes can be formed but at a very low frequency [73, 74], meaning that the two sub-genomes act largely as two separate entities. With these properties and with the fact that very little data is available for hybrids, S. cerevisiae makes a good proxy for the hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, some complex subunits may exhibit distinct evolutionary trajectories among different lineages, resulting in incompatibility when hybrids are formed 23 . This idea is corroborated by two studies that analyzed protein-protein interactions (PPIs) in protein complexes using the F1 hybrid diploids of different yeast species 62,63 . While many PPIs are conserved in hybrids, interactions involved in some biological functions related to proteostasis, metabolism, and mitochondria are specifically altered.…”
Section: Discussionmentioning
confidence: 75%